Evaluation of Efficacy and Safety of Zinobliss (Zinc Carnosine 2% and Lignocaine 2%) for the Management of Oral Mucositis and Stomatitis: A Phase 3 Prospective Randomized Open Label Multi Centric Parallel Design Study - Bijoy Deb; Vidyalakshmi Santhanam; Uma Narayanamurthy; Priyanka Raizada; Rashmi Jain; Sakthibalan Murugesan (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: Oral mucositis occurs in almost 90% of Head and Neck cancer patients receiving radiotherapy.  Zinc L carnosine, the chelation of zinc with carnosine, is beneficial for oral mucosal ulcers due to its antioxidant properties.  It also causes increased mucous production, which helps repair the injury.  The pain in oral mucositis can be addressed with the help of a local anesthetic agent, lignocaine hydrochloride.  The objective was to study the efficacy of ZINOBLISS (Zinc Carnosine 2% and lignocaine HCl 2%) for managing oral mucositis and stomatitis.Material and methods: It was an open-label, multicentric, parallel-group interventional clinical trial.  The total number of patients included in the study was 45 (each group was 15).  Arm 1 included topical administration of Zinobliss (Zinc Carnosine 2% and Lignocaine HCl 2% Gel) thrice daily for ten days or until healing, whichever was earlier.  Similarly, Arm 2 and Arm 3 included topical administration of Hexigel (Chlorhexidine Gluconate Gel) and Zytee- L (Gel containing Choline Salicylate, Lignocaine Hydrochloride, and Benzalkonium Chloride solution), respectively, thrice daily for ten days or until healing whichever was earlier.Results: The accelerated healing response in subjects treated with Zinobliss by day 4, compared to Hexigel and Zytee L, took 7 to 10 days.  Zinobliss treatment did not necessitate any modifications to the subject's diet plans.Conclusions: Zinobliss is a highly effective and well-tolerated treatment option for oral mucositis and stomatitis.